Gentamicin dosage in preterm and term neonates. - Assael, B M (1977)
Pre-dose and peak serum levels of gentamicin were measured in 82 neonates (25-42 weeks' gestational age), and for comparison in 10 infants and 9 children. Dosage was 2-2.5 mg/kg twice daily for the neonates, and three times daily for infants and children. Neonates were subdivided according to gestational age and weight. Serum levels of gentamicin were very variable in all groups. Preterm neonates of low gestational age (25-30 weeks) showed a 66% incidence of pre-dose levels exceeding 1 microgram/ml, indicating possible accumulation. In the less premature neonates this incidence was still 20-29%. The level of 4 microgram/ml, the minimum concentration required to inhibit most of the bacteria sensitive to gentamicin, was reached in increasing numbers of neonates as their gestational age rose (from 30% in the 31- to 35-week gestational age group, to 60% at term); those small-for-gestational age had consistently lower levels. It is concluded that term neonates require dosage to be individualized and serum levels of the drug to be monitored.